Penerapan Sistem Pendukung Keputusan pada Website Informasi Penginapan di Takengon dengan Metode Multi Attribute Utility Theory - Syahputra, Hendri; Sari, Fitri Sia Rifa; Gemasih, Husna (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Takengon is one of the popular tourist destinations, but visitors often face challenge in choosing accommodations that meet their preferences. The research was conducted to address this issues, with the aim of developing a web-based decision support system to assist tourists in making more accurate and efficient accommodation choices in Takengon. The research employs the Multi Attribute Utility Theory (MAUT) method, which enables the evaluations of accommodations based on various criteria such as price, facilities, ratings, reviews, location, and accommodation type. The findings show that Pintu Waluh Homestay achieved the highest MAUT score with a value of 0.757, followed by Grand Bayu Hill Hotel Takengon with a score of 0.702, and The Lavana Jejunten Bango Takengon with a score of 0.589. In conclusion, the system effectively provides objective accommodation recommendations tailored to user preferences and has the potential to increase occupancy rates in Takengon